2014
DOI: 10.12965/jer.140103
|View full text |Cite
|
Sign up to set email alerts
|

Swimming exercise ameliorates multiple sclerosis-induced impairment of short-term memory by suppressing apoptosis in the hippocampus of rats

Abstract: Multiple sclerosis is one of the autoimmune diseases in the central nervous system. Multiple sclerosis occurs through multiple mechanisms, and it is also mediated in part by an apoptotic mechanism. Swimming exercise has been recommended for the prevention and treatment of chronic diseases. In the present study, we investigated the effects of swimming exercise on short-term memory in relation with apoptotic neuronal cell death in the hippocampus following induction of multiple sclerosis. For this study, step-do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 23 publications
(33 reference statements)
2
19
0
Order By: Relevance
“…In a previous study, exercise inhibited apoptosis in various brain diseases, including Alzheimer disease and traumatic brain injury, by inhibiting Bax and caspase-3 and by activating Bcl-2. 21,27 Exercise activates various neurotrophins that promote cell survival and inhibit apoptosis. 48 In particular, apoptotic stimulation induces caspase-3 activation, but such caspase-3 activation can be blocked by BDNF.…”
Section: Kim Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, exercise inhibited apoptosis in various brain diseases, including Alzheimer disease and traumatic brain injury, by inhibiting Bax and caspase-3 and by activating Bcl-2. 21,27 Exercise activates various neurotrophins that promote cell survival and inhibit apoptosis. 48 In particular, apoptotic stimulation induces caspase-3 activation, but such caspase-3 activation can be blocked by BDNF.…”
Section: Kim Et Almentioning
confidence: 99%
“…25 In addition, exercise increases neurogenic nutrient expression 26 and inhibits neuronal cell death to improve cognitive function. 27 Several previous studies have reported that exercise influences the expression of neurotransmitters and provides support against anxiety, stress, depression, insomnia, and miscellaneous psychological disorders. In particular, neurotransmitters are associated with emotional regulation, awareness, behavior and motor control, memory and learning, temperature regulation, pain transmission, food intake, stress responses, and brain development and maturation.…”
mentioning
confidence: 99%
“…Caspase-3 is one of the most widely studies members of the caspase family and it is involved in apoptosis as the principal executor (Jin et al, 2014; Ko et al, 2009; Martin et al, 2002). Furthermore, caspase-3 is up-regulated and activated in the early-stage of apoptosis (Benchoua et al, 2001; Kang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The latency in the step-down avoidance task was determined to evaluate the short-term memory, according to the previously described method (Jin et al, 2014). The rats were trained in a step-down avoidance task on the 28 days after starting the treadmill exercise.…”
Section: Methodsmentioning
confidence: 99%
“…Apoptosis is a programmed cell death process that takes places in different cells during both embryonic and adult life (23). Exercise can either cause (24), inhibit (25) or have no effect on apoptosis of different cell types (26). The probable mechanisms responsible for exercise -induced apoptosis include: increased glucocorticoid hormone, intracellular calcium concentration and reactive oxygen species (27).…”
Section: Discussionmentioning
confidence: 99%